Transferability and use of microsatellite markers for the genetic analysis of the germplasm of some Arachis section species of the genus Arachis - Bravo, Juliana Pereira [UNESP]; Hoshino, Andrea Akemi [UNESP]; Angelici, Carla Maria Lara C.D. [UNESP]; Lopes, Catalina Romero [UNESP]; Gimenes, Marcos Aparecido [UNESP] (FapUNIFESP (SciELO), 2006)
The Arachis section is the most important of the nine sections of the genus Arachis because it includes the cultivated peanut, Arachis hypogaea. The genetic improvement of A. hypogaea using wild relatives is at an early stage of development in spite of their potential as sources of genes, including those for disease and pests resistance, that are not found in the A. hypogaea primary gene pool. Section Arachis species germplasm has been collected and maintained in gene banks and its use and effective conservation depends on our knowledge of the genetic variability contained in this material. Microsatellites are routinely used for the analysis of genetic variability because they are highly polymorphic and codominant. The objective of this study was to evaluate the transferability of microsatellite primers and the assay of genetic variability between and within the germplasm of some species of the Arachis section. Fourteen microsatellite loci developed for three different species of Arachis were analyzed and 11 (78%) were found to be polymorphic. All loci had transferability to all the species analyzed. The polymorphic loci were very informative, with expected heterozygosity per locus ranging from 0.70 to 0.94. In general, the germplasm analyzed showed wide genetic variation. © 2006 Sociedade Brasileira de Genética.
Keywords: Genetic diversity; Germplasm; Peanut; Transferability; Wild species; codominance; disease resistance; DNA extraction; gene amplification; gene locus; gene pool; gene transfer; genetic analysis; genetic conservation; genetic improvement; genetic polymorphism; genetic variability; germplasm; heterozygosity; microsatellite marker; nonhuman; nucleotide sequence; peanut; pest resistance; plant development; plant genetics; polymorphic locus; species cultivation; Arachis; Arachis hypogaea